"Womanhood, " a shared experience of participating in a lifestyle intervention with a focus on integration and physical activity to promote health among pregnant women: perspectives from pregnant women, midwives, and cultural interpreter doulas. Issue 1 (31st December 2022) - Malmström, Nina; Lydell, Marie; Carlsson, Ing-Marie
ABSTRACT: Purpose: Migrating women, have an overall increased risk of adverse outcomes and poorer health during pregnancy and childbirth. In addition, they do not participate in planned antenatal care to the same extent as natives. These disparities among migrants and native pregnant women point to the need for interventions to improve equal health and care during pregnancy and childbirth. This study aimed to explore the experiences of participating in a lifestyle intervention, named "Dancing for birth, " focusing on integration and physical activity, from the perspectives of the participating pregnant women, midwives, and cultural interpreter doulas. Method: Qualitative interviews were conducted from March 2019 to December 2020, with ten women who participated in a lifestyle intervention in Sweden: four pregnant women, three midwives, and three cultural interpreter doulas. Thematic analysis was used to analyse the data. Results: The lifestyle intervention "Dancing for birth" provided positive shared Health-promoting experiences among the participants with social inclusivness and a commitment to supporting each other. This seemed to encourage the sense of strength as a woman- a strengthboth for the individual woman and as a kind of women´s power. Conclusions: Interventions targeting physical activity, social inclusiveness, and health literacy are of utmost importance in promoting positive pregnancy experiences and equal healthcare during pregnancy. Further research is needed on how to implement antenatal education that includes all women in society.